Editorial Notes - Pokhrel, Mohan Kumar (JODEM: Journal of Language and Literature, 2025)
It is with great pleasure that we present this issue of the Journal of the Department of English Mahendra Multiple Campus, Dharan (JODEM), a platform dedicated to critical inquiry, scholarly engagement, and creative expression within the vast domain of English studies. The contributions in this volume reflect a wide range of perspectives, methodologies, and thematic concerns, demonstrating both the diversity and depth of contemporary literary and cultural study. All the Research Articles have been rigorously Peer- Reviewed by experts of the concerned domain of knowledge. Dr. Achyut Raj Kattel, in From Art to Agony: The Transformation of Aesthetic Ideals in the Ballad of Reading Gaol by Oscar Wilde explores how Wilde shifts from the celebration of beauty and art to the depiction of human suffering and moral anguish. The article highlights how aesthetic ideals are redefined through the lens of pain, justice, and existential reflection in Wilde’s text. Likewise, Dr. Jiwan Kumar Rai and Dr. Asmita Bista, in Resisting and Reconstructing the Borders of Patriarchal Culture in Pragati Rai’s Thaa†ngraa [A Creeper’s Stand], explores how the text challenges entrenched patriarchal norms and redefines the cultural boundaries of women’s identity, agency, and resistance. Similarly, Dr. Hukum Thapa, in Ecofeminism in Patricia McCormick’s Sold: Parallels between the Exploitation of Women and Nature explicates how the text interlinks the subjugation of women with the degradation of the environment, underscoring the shared structures of oppression that bind gender and ecology. In the same way, Mr. Man Kumar Rai, in Sakhewa Silli in Bantawa Rai: A Study of Indigenous Ecocriticism highlights how the ritual of Sakhewa Silli embodies ecological wisdom and cultural harmony, offering an indigenous perspective on the interconnection between nature, community, and spirituality. The article of Mr. Mohan Daungara, in Social Criticism Over Art, Culture and Space in Aldous Huxley’s Travelogues analyzes how Huxley’s travel writings critique the intersections of art, cultural practices, and spatial dynamics, exposing the underlying social tensions of modernity. Dr. Mohan Kumar Pokhrel is the next researcher, whose research article The Concept of Righteous Leadership: King Pṛthu in the Śrīmad Bhāgavata Mahāpurāṇa explores how King Pṛthu embodies the ideals of dharmic kingship through justice, responsibility, and service to his people. The article emphasizes that Pṛthu’s model of leadership, grounded in divine legitimacy and ethical governance, remains a timeless paradigm for understanding righteous authority in both ancient and modern contexts. Omi Gurung, in Women’s Rights and Empowerment Movements in Nepal: A Study of Yogmaya and Seto Dharti examine how historical and literary narratives of women’s struggles illuminate the quest for gender equality and empowerment in Nepalese society. Saraswati Katuwal, in The Female Hero’s Journey in Baniya’s Maharani: A Feminist-Archetypal Study,” analyzes the protagonist’s transformative quest as a reworking of the traditional hero’s journey from a female perspective. The article underscores how archetypal patterns and feminist insights intersect to reveal women’s resilience, agency, and struggle against patriarchal constraints. Thus, the articles included in this volume of JODEM collectively embody the journal’s mission to foster critical engagement across diverse literary, cultural, and theoretical terrains. From the transformation of aesthetic ideals in Wilde’s poetry to the challenges against patriarchal structures in contemporary Nepali fiction, from ecofeminist readings of global narratives to indigenous ecological wisdom rooted in ritual, the contributions highlight the vitality of literature as a lens through which social, cultural, and environmental realities are interrogated. Each article not only opens new pathways of interpretation but also deepens our understanding of how texts reflect, resist, and reshape the complexities of human existence. Together, these studies reaffirm the relevance of English studies as an interdisciplinary space that bridges tradition and modernity, local and global contexts, art and society. We hope that this issue stimulates further dialogue, research, and critical inquiry among scholars, students, and readers, continuing the Department’s commitment to nurturing intellectual growth and creative expression. JODEM remains a platform for both established and emerging voices, and with this issue, we once again extend an invitation to engage with the dynamic interplay of ideas that literature and criticism make possible.